Implementation of the two stay two stray learning model with a realistic mathematics education approach to mathematical understanding ability - Yanti, Rohmah; Umbara, Uba; Sunzuma, Gladys (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2025)
This study aims to determine the effectiveness of the Two Stay Two Stray (TS-TS) learning model combined with the Realistic Mathematics Education (RME) approach in improving students’ mathematical understanding. The research was conducted at SMPN 1 Sindangagung with eighth-grade students as subjects during the 2023/2024 academic year. Class VIII C was assigned as the experimental group and Class VIII D as the control group was selected using purposive sampling. This study used a quasi-experimental design with a non-equivalent pretest-posttest control group format. The instruments used included an essay test to measure mathematical understanding and teacher interview guidelines during the pre-research phase. Data analysis was carried out using normality and homogeneity tests, N-Gain calculations, and the Mann-Whitney U test. The results indicate a statistically significant difference in improvement between the two classes. Practically, the implementation of the TS-TS model based on RME increased student engagement and conceptual understanding, making it a viable alternative for designing active, collaborative, and meaningful mathematics learning.